(untitled) - Barnard, Chris (Harlow, 2001)
The aim of the course is to introduce studentsin the biological sciences to the skill of observation and enquiry, but focusing on the process of enquiry, how to formalate hypotheses and predicttions from raw information,...
Thống kê ứng dụng và viết báo cáo khoa học,Phương pháp luận nghiên cứu khoa học,Phương pháp nghiên cứu khoa học môi trường
Keywords: Science,Biology; Methodology,Methodology